The Effect Of Perceived Usefulness, Perceived Ease Of Use, Perceived Risk And Technology Readiness On Intention To Use E-Banking In Jakarta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The transaction activity of e-banking in Indonesia has showed an increased percentage of 480% in April 2020. By taking it as phenomena, this study focuses on the intention to use e-banking in Jakarta. Independent variables such as perceived usefulness, perceived ease of use, perceived risk, and technology readiness were taken to be examined. The design of this study is a quantitative reseaech. The sample size contains 94 respondents of e-banking users collected from Jakarta area. Data from respondents were measured using bivariate Pearson correlation to examine significant relationships between the variables, with the help of computer software SPSS for statistics. The findings of this research showed perceived usefulness, perceived ease of use and technology readiness having significant effect on the intention to use e-banking services..